If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1f = 12 Reorder the terms: -1f + 2x = 12 Solving -1f + 2x = 12 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-2x' to each side of the equation. -1f + 2x + -2x = 12 + -2x Combine like terms: 2x + -2x = 0 -1f + 0 = 12 + -2x -1f = 12 + -2x Divide each side by '-1'. f = -12 + 2x Simplifying f = -12 + 2x
| 3(5+4a)=63 | | 4(5+6d)=-28 | | 4(2w+7)=124 | | 6(2)-3y=12 | | 3(-6+6m)=-18 | | 2(-7-2x)=-2 | | 5(-9+4k)=135 | | 3(4+5w)=87 | | 4(3-2k)=12 | | 2(1+7k)=58 | | y+2(-2)=-8 | | 15+x=4x | | y+2(0)=-8 | | 4(1a-7)=-24 | | 6(9-x)=42 | | 6(-7+3n)=48 | | 5(6-3a)=135 | | y+2(2)=-8 | | 2(-7w-5)=-10 | | 3(-4d+2)=-18 | | 6(3a+6)=-144 | | 3x^4+x^3=6x^2+2x | | 2(7d+10)=90 | | 3(5x-4)=78 | | 4(7+6d)=244 | | 0=-3 | | 2(5x-5)=10 | | 4(-5k-10)=80 | | 4(3n+9)=24 | | 6(1x+1)=72 | | 2=-3 | | 5x-8=3x-8 |